Mechanoautophagy: Synergies Between Autophagy and Cell Mechanotransduction at Adhesive Complexes - Ravasio, Andrea; Morselli, Eugenia; Bertocchi, Cristina (Frontiers in Cell and Developmental Biology, 2022)
Cells are exposed and respond to various mechanical forces and physical cues stemming from their environment. This interaction has been seen to differentially regulate various cellular processes for maintenance of homeostasis, of which autophagy represents one of the major players. In addition, autophagy has been suggested to regulate mechanical functions of the cells including their interaction with the environment. In this minireview, we summarize the state of the art of the fascinating interplay between autophagy and the mechanotransduction machinery associated with cell adhesions, that we name ¨Mechanoautophagy¨